The Profusion of Information Systems to Combat the COVID-19 Pandemic: A Systematic Mapping of the State of the Art and Brazilian Challenges of Technological Production - Silva, Sandro Luis Freire de Castro; Nunes, Maria Augusta Silveira Netto; Fornanzin, Marcelo; dos Santos, Rodrigo Pereira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2021: Anais do XVII Simpósio Brasileiro de Sistemas de Informação, 2021)
With the arrival of COVID-19, the scientific community was mobilized, not only in researches in the biomedical field but also in searching for ways to support professionals working on the front lines of fighting the virus. In the context of information systems (IS), several systems were developed to contribute to this collective effort. In this study, we provide an overview of the profusion of systems designed to support the fight against COVID-19. To achieve this goal, a systematic mapping of the state of art was carried out in patent documents in 2020. The study compared the national technological production to the international scenario and listed the main challenges regarding technological production during COVID-19.